A quantitative approach to measure women's sexual function using electromyography: preliminary study on Kegel exercise - Mohktar, Mas Sahidayana; Ibrahim, Fatimah; Mohd Rozi, Nur Farahana; Mohd Yusof, Juhaida; Ahmad, Siti Anom; Khong, Su Yen; Omar, Siti Zawiah (International Scientific Information, 2013)
Background: Currently, the reference standard used to clinically assess sexual function among women is a qualitative questionnaire. Hence, a generalised and quantitative measurement tool needs to be available as an alternative. This study investigated whether an electromyography (EMG) measurement technique could be used to help quantify women's sexual function.